Multi-Element Profile Characterization in Monofloral Honey - Kriss Davids Labsvards; Anastasija Borisova; Kristina Kokina; Maris Bertins; Arturs Viksna; Vita Rudovica (Proceedings)
Apiculture, in general, is an important sector of the national economy due to the environmental benefits of pollination [...]